Correction to “Energy Efficient Signal Detection Using SPRT and Ordered Transmissions in Wireless Sensor Networks” - Shailee Yagnik; Ramanarayanan Viswanathan; Lei Cao (IEEE Open Journal of Signal Processing)
In [1, p. 1124], a footnote is needed on (13) as shown below: \begin{equation*}\qquad\qquad\quad{{α }^# } < \left( {1 - {{c}_1}} \right)α + \left( {1 - \left( {1 - {{c}_1}} \right)α } \right)α\qquad\qquad\quad \hbox{(13)$^{1}$} \end{equation*}